x(-13-x)=42

Simple and best practice solution for x(-13-x)=42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(-13-x)=42 equation:


Simplifying
x(-13 + -1x) = 42
(-13 * x + -1x * x) = 42
(-13x + -1x2) = 42

Solving
-13x + -1x2 = 42

Solving for variable 'x'.

Reorder the terms:
-42 + -13x + -1x2 = 42 + -42

Combine like terms: 42 + -42 = 0
-42 + -13x + -1x2 = 0

Factor out the Greatest Common Factor (GCF), '-1'.
-1(42 + 13x + x2) = 0

Factor a trinomial.
-1((7 + x)(6 + x)) = 0

Ignore the factor -1.

Subproblem 1

Set the factor '(7 + x)' equal to zero and attempt to solve: Simplifying 7 + x = 0 Solving 7 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + x = 0 + -7 x = 0 + -7 Combine like terms: 0 + -7 = -7 x = -7 Simplifying x = -7

Subproblem 2

Set the factor '(6 + x)' equal to zero and attempt to solve: Simplifying 6 + x = 0 Solving 6 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + x = 0 + -6 x = 0 + -6 Combine like terms: 0 + -6 = -6 x = -6 Simplifying x = -6

Solution

x = {-7, -6}

See similar equations:

| 4+12t=8-16t | | 3*ln(x)+2*x=3*ln(20)+ln(10) | | -6(x-4)=-3(x-2) | | -10x+1-7=-17x+7 | | (4y-5)(6+y)=0 | | -3=27a-3(2a-3) | | ln(2x+11)=0 | | 9x-1+1x=3 | | 2t-4+4t=6t-4 | | 6x^2+y^2=1 | | 70n^2=30+8n | | -5(1-5x)+5(-8x-2)=-4x+8x | | 5(x+6)=14x-4x+10 | | 20x^4y+25x^2=0 | | 8x^3y^5-12x^2y^8+36x^4y^10=0 | | X^4=54 | | 14x-3=14-3x | | -(-1+10y)=-20-31y | | l(20-l)=36 | | -4.9*x^2+9.8x+0=3.675 | | Y=18x^2+81 | | 14x+2x=12x+6+10x | | 100x^2+25=0 | | 14x+3x+10x=6 | | log[4](2x-3)=3 | | 5r-29=-23+3r | | 3(x+4y)+7y=6 | | 289.80=9(0.08m+22.80+0.10(22.80)) | | 14x+2x=3x+6+10x | | Y^2-32y+175=0 | | 2(3x-2)+4=30-3x | | 2x+7-3x=25+2x |

Equations solver categories